2023
DOI: 10.3389/fneur.2023.1090878
|View full text |Cite
|
Sign up to set email alerts
|

Associations between anxiety, depression with migraine, and migraine-related burdens

Abstract: BackgroundAnxiety and depression are the most common psychiatric comorbidities in migraine, but their impact on the risk of developing migraine and their gender and age differences are unclear, and research on their associations with migraine-related burdens are limited.ObjectiveTo systematically explore the association between anxiety and depression with migraine and migraine-related burdens, including the risk of developing migraine, as well as migraine frequency, severity, disability, headache impact, quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
0
3
0
1
Order By: Relevance
“…Finally, PSQI score and Qi depression score were demonstrated as significant independent risk factors of migraine. Two of our previous studies found that the PSQI score, SAS score, and SDS score were all significantly and positively associated with the risk of migraine, with the PSQI score having the relatively best predictive power for migraine [ 23 , 24 ]. The results of this study showed that the AUCs of PSQI score, SAS score, and SDS score for migraine were 0.83 (95% CI: 0.77–0.89), 0.75 (95% CI: 0.68–0.83), and 0.61 (95% CI: 0.52–0.69), respectively, which were similar to our previous studies and further demonstrated that the PSQI score had the relatively best predictive ability for migraine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, PSQI score and Qi depression score were demonstrated as significant independent risk factors of migraine. Two of our previous studies found that the PSQI score, SAS score, and SDS score were all significantly and positively associated with the risk of migraine, with the PSQI score having the relatively best predictive power for migraine [ 23 , 24 ]. The results of this study showed that the AUCs of PSQI score, SAS score, and SDS score for migraine were 0.83 (95% CI: 0.77–0.89), 0.75 (95% CI: 0.68–0.83), and 0.61 (95% CI: 0.52–0.69), respectively, which were similar to our previous studies and further demonstrated that the PSQI score had the relatively best predictive ability for migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Migraine is known to be associated with a variety of sleep disorders and psychiatric disorders, such as anxiety and depression, and the bidirectional relationship between migraine and these disorders is of increasing interest to researchers [ 7 , 18 22 ]. Our previous studies showed that poor sleep quality, anxiety, and depression were significantly and positively associated with increased risk of migraine and migraine burdens, and that Pittsburgh Sleep Quality Index (PSQI) score, Zung's Self-rating Anxiety Scale (SAS) and Self-rating Depression Scale (SDS) scores had good predictive value for migraine and could be used as potential predictors for migraine [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hala ere badakigu, estres kronikoa antsietatearekin eta depresioarekin gehien lotzen den faktorea dela [2]. Ikerketa berri baten arabera, antsietatea eta depresioa, eta nahasmendu hauek eragin dezaketen estresa, migraina pairatzeko arrisku altuagoarekin eta migrainarekin lotutako kargekin (loaren kalitate eskasa, ezgaitasun edota buruko min larriak) modu independentean erlazionaturik daude [3]. Are gehiago, bi fenomeno hauen arteko bi noranzkoetako harremana definitu dute.…”
Section: Sarreraunclassified
“…Recent evidence indicates a bidirectional relationship between migraine and mental health disorders [ 7 ]. Individuals experiencing depression and anxiety are noted to have an elevated likelihood of encountering migraine, underscoring the importance of gaining a comprehensive understanding of these concurrent conditions.…”
Section: Introductionmentioning
confidence: 99%